Social Capital and Health in Australia: An Overview from the Household, Income and Labour Dynamics in Australia Survey - Berry, H; Welsh, J; Welsh, J.A (My University, 2010)
Social capital is associated with better health, but components of social capital and their associations with different types of health are rarely explored together. The aim of this study was to use nationally representative data to develop population norms of community participation and explore the relationships between structural and cognitive components of social capital with three forms of health – general health, mental health and physical functioning. Data were taken from Wave 6 (2006) of the Household, Income and Labour Dynamics in Australia Survey. Using individual-level data, the structural component of social capital (community participation) was measured using a twelve-item short-form of the Australian Community Participation Questionnaire, and the cognitive component (social cohesion) by sense of belonging, tangible support, trust and reciprocity. Three subscales of the SF-36 provided measures of health. Multiple hierarchical regression modelling was used to investigate multivariate relationships among these factors. Higher levels of participation were related to higher levels of social cohesion and to all three forms of (better) health, particularly strongly to mental health. These findings could not be accounted for by sex, age, Indigenous status, education, responsibility for dependents, paid work, living alone or poverty. Controlling for these and physical health, structural and cognitive components of social capital were each related to mental health, with support for a possible mediated relationship between the structural component and mental health. Social capital was related to three forms of health, especially to mental health. Notable gender differences in this relationship were evident, with women reporting greater community participation and social cohesion than men, yet worse mental health. Understanding the mechanisms underlying this apparent anomaly needs further exploration. Because community participation is amenable to intervention, subject to causal testing, our findings may assist in the development of programs which are effective in promoting social cohesion and, thereby, mental health.
Social Science & Medicine
Keywords: Health; Social Capital; Health and wellbeing; Social Capital; Health; Health and wellbeing